PENERAPAN KURIKULUM MERDEKA BELAJAR PADA KARAKTER DISIPLIN SISWA KELAS V DI SDN PONDOK BETUNG 04 - Fitria Rosmi; Aliya Zakiya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the formation of a low level of discipline character, because there are still some students who have obstacles, many students are not disciplined in the learning process. Therefore, the implementation of the independent learning curriculum is a solution to form students' disciplined character. This study aims to determine how the implementation of the independent learning curriculum on disciplined character and to determine the inhibiting factors. The research was conducted at SDN Pondok Betung 04, with a qualitative research methodology. Data collection techniques were carried out through observation, interviews, and documentation studies. The number of respondents was 6 people consisting of 1 homeroom teacher and 5 students. The data analysis technique was carried out using the triangulation technique (data collection, data reduction, data presentation, and drawing conclusions). Based on the results of the study, it was revealed that the implementation of the independent curriculum was carried out with a flexible and student-centered approach. Some of the inhibiting factors are the lack of self-awareness in students regarding disciplined character and the presence of disturbances in the classroom such as not being disciplined when entering the classroom after the ceremony, being lazy to do the picket task, and students not doing assignments on time. The results of this study can be useful for teachers in improving disciplined character.